2016
DOI: 10.3892/ol.2016.4980
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 is overexpressed in human laryngeal carcinoma and contributes to the proliferation of HEp2 cells

Abstract: Ki-67 is one of the most useful markers to evaluate cell proliferative activity and has been widely used in tumor treatment and research. However, its role in human laryngeal carcinoma remains poorly defined. The aim of the present study was to investigate the expression of Ki-67 in human laryngeal squamous carcinoma and the effect of Ki-67 gene silencing by small interfering (si)RNA on the proliferation of human laryngocarcinoma HEp2 cells. Immunohistochemistry and reverse transcription-quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…To further confirm this finding, we determined the Ki-67 level, which reflects active cell proliferation. 27 Consistently, we observed fewer Ki-67-positive cells when E6, WNT4, and JIP2 were knocked down (Fig. 3c, d and Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
“…To further confirm this finding, we determined the Ki-67 level, which reflects active cell proliferation. 27 Consistently, we observed fewer Ki-67-positive cells when E6, WNT4, and JIP2 were knocked down (Fig. 3c, d and Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
“…HNSCCs encompass cancers generated from oral cavity, oropharynx, nasopharynx, hypopharynx, larynx, and sinus. Significantly, laryngeal squamous cell carcinoma is among the most malignant cancers and accounts for 1%–2.5% of all malignancies [ 2 ], while limited-stage HNSCCs are often curable with surgical resection or definitive radiotherapy and chemotherapy, such as platinum-based regimens, recurrent, and metastatic HNSCCs are associated with poor prognosis, with a 1-year survival rate of approximately 50% [ 3 ]. Indeed, the 5-year overall survival rate of laryngeal cancer is less than 60% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study by De Vincentiis and Bai demonstrated increased expression of the Ki-67 proliferative index in both patients with poorly differentiated carcinomas and patients with regional lymph node metastases [11, 12]. In contrast to the above, these results were not confirmed by other authors [13, 14].…”
Section: Introductionmentioning
confidence: 84%
“…Their review strongly suggests that immunohistochemical staining of Ki-67 correlates with tumoral aggressiveness and worse prognosis in patients [16]. Ki-67 can be used as an important indicator for judging clinical progress and estimating prognosis in human laryngeal squamous carcinoma [12].…”
Section: Introductionmentioning
confidence: 99%